Antiviral treatment for viral pneumonia: current drugs and natural compounds - Hao Zhang; Chunxia Ge; David Fisher; Nguyen Thi Thu Hien; Erkin Musabaev; Khrystyna Pronyuk; Yin Xia; Zhide Zhu; Yan Wang; Yiping Dang; Lei Zhao (Virology Journal, 2025)
Abstract In recent years, viral pneumonia has become a significant challenge to global public health, particularly during the COVID-19 pandemic. Viral pneumonia can be caused by various viruses, including influenza virus, RSV, and adenovirus. These viruses trigger inflammatory responses by invading the respiratory epithelial cells, leading to lung damage. Existing antiviral drugs such as ribavirin, adobiravir, and oseltamivir exert their therapeutic effects by inhibiting different stages of the viral life cycle but face issues such as increasing drug resistance. Natural components like astragalus saponins, Houttuynia cordata flavonoids, and tea theaflavin-gallates have demonstrated supportive roles in antiviral treatments, capable of not only enhancing immune responses but also potentially inhibiting viral replication through multiple pathways, thereby alleviating lung damage. Although natural components cannot entirely replace traditional antiviral drugs, their role in comprehensive treatment regimens is becoming increasingly important. This review summarizes the current applications and limitations of antiviral drugs and explores the research progress and potential mechanisms of natural components in the treatment of viral pneumonia.